THE EFFECT OF RESISTANCE TRAINING AND ANTIOXIDANT SUPPLEMENTATION WITH ASTAXANTHIN ON PLASMA MALONDIALDEHYDE (MDA) LEVELS IN ADULTS - Limyati, Yenni; Rahmia, Puteri; Hutapea, Albert Manggading (Syntax Corporation Indonesia, 2025)
Resistance training has grown in importance for managing oxidative stress, particularly in adults, as it enhances muscle development and overall health. However, it also leads to the formation of reactive oxygen species (ROS), which can result in cellular oxidative damage and potentially hasten the aging process. This review assesses the role of astaxanthin, a powerful antioxidant, in counteracting oxidative stress during resistance training, with a focus on its effects on aging. This study employs a narrative review methodology, evaluating peer-reviewed publications from 2019 to 2024. Keywords used include